2019
DOI: 10.2147/ott.s207211
|View full text |Cite
|
Sign up to set email alerts
|

<p>Protein kinase C-iota-mediated glycolysis promotes non-small-cell lung cancer progression</p>

Abstract: Purpose To determine whether protein kinase C-iota (PKC-iota) is associated with glucose metabolism in non-small-cell lung cancer (NSCLC) and whether its regulatory effect on metabolic and biological changes observed in NSCLC can be mediated by glucose transporter 1 (GLUT1). Patients and methods Forty-five NSCLC patients underwent combined 18 F-fludeoxyglucose ( 18 F-FDG) positron emission tomography and computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…It was investigated that glycolysis was regulated by the long non-coding RNA HOTTIP/ miR-615-3p/HMGB3 axis to impact tumor cell behaviors in non-small cell lung carcinoma (45). Another study revealed that glycolysis metabolism could be controlled by protein kinase C-iota, due to the progression of non-small-cell lung carcinoma (46). PCK1 is another gene that participates in cell glycolysis metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It was investigated that glycolysis was regulated by the long non-coding RNA HOTTIP/ miR-615-3p/HMGB3 axis to impact tumor cell behaviors in non-small cell lung carcinoma (45). Another study revealed that glycolysis metabolism could be controlled by protein kinase C-iota, due to the progression of non-small-cell lung carcinoma (46). PCK1 is another gene that participates in cell glycolysis metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, β-AR activation depressed endothelial oxidative phosphorylation and turned on the angiogenic switch for tumor progression in a rodent prostate cancer model (Zahalka et al, 2017). Additionally, the activations of PKC and PKA can lead to unfavorable metabolic alterations and fuel cancer progression (Aggarwal et al, 2019;Liu et al, 2019;Vergara et al, 2020).…”
Section: Metabolismmentioning
confidence: 99%
“…Glut1, HK2, and LDH-A proteins are key molecules in the glycolysis process of cancer cells, which can affect the glucose uptake and lactic acid production of cancer cells. 24 However, up-regulation of FOXO6 expression can significantly promote glycolysis in HCC cells. Some studies 25 suggested that FOXO6 produced a marked effect in the metabolism of cancer cells, which was validated in the present study.…”
Section: Discussionmentioning
confidence: 99%